Auricles Anomalies in Patients With a TCF12 Gene Mutation. Issue 1 (22nd January 2023) - Lacroix, Guillaume; Karnoub, Melodie-Anne; Vinchon, Matthieu; Wolber, Alexis; Martinot, Véronique; Guerreschi, Pierre
Abstract : Craniostenosis is a morphological anomaly affecting about 0.5 of 1000 births and one third of the cases are of genetic origin. Among the syndromes responsible for craniostenosis, there is the Saethre-Chotzen syndrome due to a mutation of the TWIST 1 gene located on chromosome 7. This polymalformative syndrome classically includes a particular morphology of the auricles. The penetrance is variable and results in a phenotypic variability at the origin of "Saethre-Chotzen like" clinical pictures for which the TWIST 1 gene mutation is sometimes not found. Recently, the TCF 12 gene has been implicated in some of these cases. Among the multiple facial malformations, we have carefully examined the particular morphology of the auricle of these patients. The authors found several abnormalities in patients with a TCF 12 gene mutation, namely a thickened and hammered upper pole of the helix, a narrow concha without crux cymbae and a thickened lobe. These morphological features may guide the diagnosis and allow an earlier search for a TCF 12 gene mutation.